Serbia : School Finance - World Bank (Washington, DC, 2014)
In support of the multi-annual efforts of the Government of Serbia to advance financing policies and practice in the education sector, the World Bank conducted a review of policies related to school finance along the Systems Approach for Better Education Results, or SABER-school finance framework. School finance policy goals are observed in the following areas: the basic conditions for learning, monitoring learning conditions and outcomes, overseeing service delivery, budgeting with adequate and transparent information, providing more resources to students who need them, and managing resources efficiently. This report presents findings on the strengths and weaknesses of the school finance system in Serbia. It discusses the need to use more efficiently the public expenditure available for education in the country, and it looks at the policy goals in financing public education more broadly.